Efektivitas Program Penanganan Sampah Plastik dalam Mengurangi Timbulan Sampah di Kelurahan Wonorejo Kecamatan Marpoyan Damai Kota Pekanbaru - Sufian Hamim; Fadhli Rizgullah Putra; Abel Gurifno; Sukron Mayee (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
The problem of plastic waste is one of the environmental challenges faced by various regions in Indonesia, including the city of Pekanbaru. The increase in population and community activities causes the generation of plastic waste to continue to increase from year to year. Wonorejo Village, Marpoyan Damai District is one of the areas that faces waste management problems so an effective handling program is needed. This study aims to analyze the effectiveness of plastic waste handling programs in reducing waste generation in Wonorejo Village, Marpoyan Damai District, Pekanbaru City. This study uses a Public Administration approach with the theory of effectiveness of the Duncan program which includes goal achievement, integration, and adaptation. The research method used is a descriptive qualitative approach through literature study and analysis of various previous studies. The results of the study show that the effectiveness of the plastic waste management program is influenced by community participation, government support, availability of facilities and infrastructure, and sustainable waste management innovations. Therefore, it is necessary to strengthen coordination between actors and increase public awareness to realize effective and sustainable plastic waste management.